1994
DOI: 10.1021/bi00203a026
|View full text |Cite
|
Sign up to set email alerts
|

Extensively Methylated Myosin Subfragment-1: Examination of Local Structure, Interactions with Nucleotides and Actin, and Ligand-Induced Conformational Changes

Abstract: The atomic structure of myosin subfragment-1 (S1) has been recently solved for crystals of extensively methylated S1 [Rayment et al. (1993) Science 261, 50-58]. In this study, the effect of such a modification on S1 structure and function was examined. According to the far- and near-ultraviolet CD spectra, the methylation does not affect the secondary structure of S1 but causes limited changes in its tertiary structure. The methylation significantly decreases the affinity of S1 for actin in rigor and, to a les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
(82 reference statements)
3
6
0
Order By: Relevance
“…The Mg 2+-and Ca 2+-ATPase activities of $1 were enhanced by methylation sixfold and three-fold, respectively, while the K+-EDTAATPase activity was almost abolished (10-15% of the control). These changes in ATPase activities are similar to those described in the literature (Bivin et al, 1994;Phan et al, 1994).…”
Section: Protein Preparationssupporting
confidence: 90%
See 1 more Smart Citation
“…The Mg 2+-and Ca 2+-ATPase activities of $1 were enhanced by methylation sixfold and three-fold, respectively, while the K+-EDTAATPase activity was almost abolished (10-15% of the control). These changes in ATPase activities are similar to those described in the literature (Bivin et al, 1994;Phan et al, 1994).…”
Section: Protein Preparationssupporting
confidence: 90%
“…These our results are well consistent with recently published data of Phan and colleagues (1994) demonstrating that the methylafion, like the trinitrophenylation of Lys-83, accelerates the dissociation of a nucleotide trapped on $1 by vanadate or beryllium fluoride, strongly impairs the coupling between the actin-and nucelotide-binding sites, and perturbs the spread of nucelotide-induced conformational changes throughout the $1 structure. The authors suggested that these methylation-caused changes in the $1 molecule are due to the methylation of Lys-83 (Phan et al, 1994), and our results support this assumption. On the other hand, the methylation-induced decrease of the $1 thermal stability is related, most likely, to the modification of lysine residues different from Lys-83.…”
Section: Effects Of Different Modificationssupporting
confidence: 87%
“…The pattern of inhibition of K+(EDTA)-ATPase and activation of divalent cation-dependent ATPase agrees with that previously reported by Kitagawa et al (1961) for reaction of a single lysyl E-NH2 group with 2,4,6-trinitrobenzenesulfonate and is typical of the effect of a number of myosin modifiers. The effect of methylation on ATPase activities reported here is also quite similar to several of those recently reported by Phan et al (1994); however, because the latter authors did not carry out an amino acid analysis of the methylated protein, it is difficult to make a direct comparison. When S1 [isolated from the central portion of the Q Sepharose peak (Fig.…”
Section: The Rg Of Sisupporting
confidence: 87%
“…It is known that dimethyllysine residues in proteins are not cleaved by trypsin at a significant rate, whereas reductive methylation of trypsin itself does not reduce its catalytic activity (Means, 1977). Although Phan et al (1994) reported increased susceptibility to heat denaturation after methylation of S1, reductive alkylation has been reported to stabilize chymotrypsinogen A (Fujita and Noda, 1991) and glycogen phosphorylase b (Shatsky et al, 1973) to denaturation, possibly by increasing the hydrophobicity of lysine E-amino groups. Resistance to proteolysis may have been a contributing factor in the successful crystallization of reductively methylated S1.…”
Section: Rigid-body Rotatonmentioning
confidence: 99%
“…It remained to be determined, however, whether the reductive alkylation had significantly altered the relative arrangement of domains within myosin. Recently, the use of the X-ray structure as a model for the contractile cycle has been questioned due to the changes in the enzymatic properties of the molecule induced by reductive methylation (Bivin et al, 1994;Phan et al, 1994).…”
mentioning
confidence: 99%